Hubungan Status Gizi dengan Kejadian Anemia pada Remaja Putri di SMA PGRI 4 Banjarmasin - Khalilah Adiyani; Farida Heriyani; Lena Rosida (Homeostasis, 2018)
Abstract:Young women are said to be anemic if Hb levels <12 g/dl.World Health Organization >30% or 2 billion people in the world are having anemia status. Lack of micronutrients such as: iodine, vitamin A and iron in the diet can cause anemia. This study aims to determine the relationship of nutritional status with the incidence of anemia in female adolescents in PGRI 4 High School Banjarmasin in 2017. This research is analytic observational with cross sectional approach. Samples were taken with proportional stratified random sampling technique, consisted of 67 research subjects. Data analysis used chi square test. The results showed that 62.7% had anemia, 37.3% had no anemia, 9% nutritional status was poor, and 91% of nutritional status was normal overweight. The results showsed p value= 1.000 (p> 0.005). Conclusion of this research is there is no significant relationship between nutritional status with the incidence of anemia in female adolescents in PGRI 4 high school Banjarmasin. Keywords: nutritional status, anemia, female adolescent. Abstrak: Remaja putri dikatakan anemia jika Hb <12 g/dl. World Health Organization melaporkan >30% atau 2 miliar orang di dunia berstatus anemia. Kekurangan zat gizi mikro seperti: yodium, vitamin A dan zat besi dalam makanan dapat menyebabkan anemia. Penelitian ini bertujuan mengetahui hubungan status gizi dengan kejadian anemia pada remaja putri di SMA PGRI 4 Banjarmasin tahun 2017. Penelitian ini bersifat observasional analitik dengan pendekatan cross sectional. Sampel diambil dengan teknik proportional stratifiedrandom sampling, terdiri dari 67 subjek penelitian. Analisis data menggunakan uji chi square. Hasil penelitian menunjukkan distribusi subjek penelitian 62,7% mengalami anemia, 37,3% tidak mengalami anemia, 9% status gizi kurus, dan 91% status gizi normal gemuk. Hasil analisis data menunjukkan nilai p= 1,000 (p> 0,005). Simpulan, tidak terdapat hubungan yang bermakna antara status gizi dengan kejadian anemia pada remaja putri di SMA PGRI 4 Banjarmasin. Kata-kata kunci: status gizi, anemia, remaja putri